Analytic element modeling of groundwater flow - Haitjema, H. M. (Henk M.) (Academic Press, 1995)
Modeling has become an essential tool for the groundwater hydrologist. Where field data is limited, the analytic element method (AEM) is rapidly becoming the modeling method of choice, especially given the availability of affordable modeling software. Analytic Element Modeling of Groundwater Flow provides all the basics necessary to approach AEM successfully, including a presentation of fundamental concepts and a thorough introduction to Dupuit-Forchheimerflow. This book is unique in its emphasis on the actual use of analytic element models. Real-world examples complement material presented in the text. An educational version of the analytic element program GFLOW is included to allow the reader to reproduce the various solutions to groundwater flow problems discussed in the text. Researchers and graduate students in groundwater hydrology, geology, andengineering will find this book an indispensable resource. * * Provides a fundamental introduction to the use of the analytic element method. * Offers a step-by-step approach to groundwater flow modeling. * Includes an educational version of the GFLOW modeling software.